Comparison of minimally invasive and traditional surgical approaches for refractory mesial temporal lobe epilepsy: A systematic review and meta‐analysis of outcomes. (3rd March 2021) - Kohlhase, Konstantin; Zöllner, Johann Philipp; Tandon, Nitin; Strzelczyk, Adam; Rosenow, Felix
Abstract: Magnetic resonance‐guided laser interstitial laser therapy (MRgLITT) and radiofrequency ablation (RFA) represent two minimally invasive methods for the treatment of drug‐refractory mesial temporal lobe epilepsy (mTLE). We performed a systematic review and a meta‐analysis to compare outcomes and complications between MRgLITT, RFA, and conventional surgical approaches to the temporal lobe (i.e., anterior temporal lobe resection [ATL] or selective amygdalohippocampectomy [sAHE]). Forty‐three studies (13 MRgLITT, 6 RFA, and 24 surgery studies) involved 554, 123, 1504, and 1326 patients treated by MRgLITT, RFA, ATL, or sAHE, respectively. Engel Class I (Engel‐I) outcomes were achieved after MRgLITT in 57% (315/554, range = 33.3%–67.4%), RFA in 44% (54/123, range = 0%–67.2%), ATL in 69% (1032/1504, range = 40%–92.9%), and sAHE in 66% (887/1326, range = 21.4%–93.3%). Meta‐analysis revealed no significant difference in seizure outcome between MRgLITT and RFA ( Q  = 2.74, p  = .098), whereas ATL and sAHE were both superior to MRgLITT (ATL: Q  = 8.92, p  = .002; sAHE: Q  = 4.33, p  = .037) and RFA (ATL: Q  = 6.42, p  = .0113; sAHE: Q  = 5.04, p  = .0247), with better outcome in patients at follow‐up of 60 months or more. Mesial hippocampal sclerosis (mTLE + hippocampal sclerosis) was associated with significantly better outcome after MRgLITT (Engel‐I outcome in 64%; Q  = 8.55, p  = .0035). The rate of major complications was 3.8% for MRgLITT, 3.7% for RFA, 10.9% for ATL, and 7.4% for sAHE; the differences did not show statistical significance. Neuropsychological deficits occurred after all procedures, with left‐sided surgeries having a higher rate of verbal memory impairment. Lateral functions such as naming or object recognition may be more preserved in MRgLITT. Thermal therapies are effective techniques but show a significantly lower rate of Engel‐I outcome in comparison to ATL and sAHE. Between MRgLITT and RFA there were no significant differences in Engel‐I outcome, whereby the success of treatment seems to depend on the approach used (e.g., occipital approach). MRgLITT shows a similar rate of complications compared to RFA, whereas patients undergoing MRgLITT may experience fewer major complications compared to ATL or sAHE and might have a more beneficial neuropsychological outcome.